2020
DOI: 10.21203/rs.3.rs-46176/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of unilateral and bilateral polymethylmethacrylate-augmented cannulated pedicle screw fixation for the management of lumbar spondylolisthesis with osteoporosis

Abstract: Background: Cannulated pedicle screw (CPS) augmented by polymethylmethacrylate (PMMA) can achieve satisfactory clinical efficacy in the treatment of lumbar spondylolisthesis with osteoporosis. However, accurate application of CPSs will help to avoid the difficulty of screw revision and reduce the incidence of PMMA-related complications. This study aimed to investigate the mid-term efficacy of CPS compared to unilateral and bilateral applications in this common lumbar degenerative disease.Methods: Between May 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…(preoperative slippage - postoperative slippage) / preoperative slippage × 100% [10]. The spondylolisthesis rate at 2 weeks and 1 year after operation was measured by Taillard’s measurement [11], and the reduction loss rate was also calculated. In addition, we observed the condition of the fusion of bone graft and checked the instrumentation 2 weeks and 1 year after the operation [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…(preoperative slippage - postoperative slippage) / preoperative slippage × 100% [10]. The spondylolisthesis rate at 2 weeks and 1 year after operation was measured by Taillard’s measurement [11], and the reduction loss rate was also calculated. In addition, we observed the condition of the fusion of bone graft and checked the instrumentation 2 weeks and 1 year after the operation [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…С учетом высокой частоты экстравазации ПММА (34,52 %) при увеличении числа оперированных уровней может быть полезна селективная цементная аугментация концевых позвонков [34]. При этом односторонняя цементная аугментация обеспечивает клинические исходы не хуже, чем двусторонняя, с меньшим временем операции, кровопотерей и частотой формирования затеков [35]. Клинический опыт применения ПММА при дегенеративных поражениях поясничного отдела позвоночника и сниженной МПКТ представлен в табл.…”
Section: результатыunclassified
“…17,18 Polymethylmethacrylate (PMMA)-augmented cannulated pedicle screws (CPSs) have been established as a safe alternative to traditional techniques and are frequently implemented in this patient population. 19,20 Liu et al 21 reported outcome data from both unilateral and bilateral PMMAaugmented CPSs and demonstrated significant improvement in VAS (decrease from approx. 8 to 2) and ODI (decrease from approx.…”
mentioning
confidence: 99%